(untitled) (Global Conference on Medical and Health Sciences, 2026)
Neurological disorders — including stroke, epilepsy, Parkinson’s disease, and headache — impose a disproportionate burden in low- and middle-income countries where access to specialist neurology care is severely constrained by workforce shortages and geographic barriers. Teleneurology — the delivery of neurological diagnostic and management services through video consultation, store-and-forward image transmission, and digital decision support — offers a scalable mechanism for extending specialist neurology care to underserved populations. This review analyses 45 studies of teleneurology programmes published between 2015 and 2024, with particular focus on evidence from low- and middle-income country settings and implications for Uzbekistan. Telestroke networks have demonstrated door-to-needle time reductions of 15–35 minutes and equivalent thrombolysis outcomes to in-person assessment, with implementation in over 50 countries. Tele-epilepsy and tele-Parkinson programmes demonstrate equivalent diagnostic accuracy and treatment quality to in-person consultation for appropriate patient populations. Implementation challenges including digital infrastructure, regulatory frameworks, and clinical acceptance are evaluated.